Entrepreneurial intent among prospective graduates of higher education institution: An exploratory investigation in Kafa, Sheka, and Bench-Maji Zones, SNNPR, Ethiopia - Edomgenet Hiba Issa; Zerebruk Zewdu Tesfaye (Journal of Innovation and Entrepreneurship, 2020)
The purpose of this paper is to present results of an exploratory study conducted on entrepreneurial intent among graduating class students of higher education institutions in Kafa, Sheka, and Bench-Maji Zones, Southern Nation Nationalities Peoples' Region (SNNPR), Ethiopia. The research design of the study was a cross-sectional survey design where relevant data were collected through questionnaires from a sample of 347 University and Technical and Vocational Education and Training (TVET) College graduating class students.The data were analyzed using both descriptive statistics (bar graph and pie chart) and inferential statistics (chi-square goodness-of-fit test, independent samplest test, and one-way between-group analysis of variance). The study found out that among prospective graduates of higher education institutions in the study area, only 45.4-50.6% had low, 24-33.7% had moderate, and 18-25% had a high level of entrepreneurial intent. The study also showed that the level of higher education, prior experience of self-employment, and the chance of taking extra curricular entrepreneurship courses were the three demographic and other distal variables that explained the difference in entrepreneurial intent among the study population. The study, however, showed gender, the chance of taking entrepreneurship courses as part of curriculum, college, department, parent'soccupation, and level of education had no statistically significant association withentrepreneurial intent of the study population. The study is expected to hold relevant inputs to politicians and national policy-makers, the Ministry of Science and Higher Education, entrepreneurial intent researchers, and model developers.
Keywords: 650; Entrepreneurial intent; Demographic variables; Gender; University; TVET College; Department; Entrepreneurship education; Prior experience in self-employment; parents' occupation and education